Epidermal Growth Factor Protects Against High Glucose-Induced Podocyte Injury Possibly via Modulation of Autophagy and PI3K/AKT/mTOR Signaling Pathway Through DNA Methylation - Sun Y (Dove Medical Press, 2021)
Yan Sun,1 Ming Deng,2 Xiao Ke,2 Xiangyang Lei,3 Hao Ju,3 Zhiming Liu,3 Xiaosu Bai3,4 1Department of Endocrinology, Southern University of Science and Technology Hospital, Shenzhen, People’s Republic of China; 2Department of Cardiology, Fuwai Hospital, Chinese Academy of Medical Sciences, Shenzhen Sun Yat-Sen Cardiovascular Hospital, Shenzhen, 518057, People’s Republic of China; 3Department of Endocrinology, Affiliated Longhua People’s Hospital, Southern Medical University, Longhua People’s Hospital, Shenzhen, People’s Republic of China; 4Department of General Practice; Affiliated Longhua People’s Hospital, Southern Medical University, Longhua People’s Hospital, Shenzhen, People’s Republic of ChinaCorrespondence: Xiaosu BaiAffiliated Longhua People’s Hospital, Southern Medical University, Longhua People’s Hospital, No. 2, Jianshe East Road, Bao’an District, Shenzhen, 518109, People’s Republic of ChinaTel +86-755-27741585Email bxsllb@163.comAim: Diabetic nephropathy (DN) is a serious health problem worldwide. Epidermal growth factor (EGF) has suggested as a potential biomarker for the progression of chronic kidney disease. In this study, we examined the effects of EGF on the high glucose (HG)-induced podocyte injury and explored the underlying molecular mechanisms.Methods: The cell proliferation, toxicity, and cell apoptosis of podocytes were determined by CCK-8 assay, lactate dehydrogenase release assay, and flow cytometry, respectively, and protein levels in the podocytes were determined by Western blot assay. Mechanistically, DNA methylation analysis, bioinformatic analysis, methylation‑specific PCR and quantitative real-time PCR were used to analyze functional pathways in differentially methylated genes and the expression of the key methylated genes in the podocytes after different interventions.Results: EGF treatment significantly increased the protein expression level of LC3 and decreased the protein level of P62 in HG-stimulated podocytes, which was attenuated by autophagy inhibitor, 3-methyladenine. EGF increased the cell proliferation and the protein expression levels of nephrin and synaptopodin, but reduced cell toxicity and cell apoptosis and protein expression level of cleaved caspase-3, which was partially antagonized by 3-methyladenine. DNA methylation expression profiles revealed the differential hypermethylation sites and hypomethylation sites among podocytes treated with normal glucose, HG and HG+EGF. GO enrichment analysis showed that DNA methylation was significantly enriched in negative regulation of phosphorylation, cell-cell junction and GTPase binding. KEGG pathway analysis showed that these genes were mainly enriched in PI3K-Akt, Hippo and autophagy pathways. Further validation studies revealed that six hub genes (ITGB1, GRB2, FN1, ITGB3, FZD10 and FGFR1) may be associated with the protective effects of EGF on the HG-induced podocyte injury.Conclusion: In summary, our results demonstrated that EGF exerted protective effects on HG-induced podocytes injury via enhancing cell proliferation and inhibiting cell apoptosis. Further mechanistic studies implied that EGF-mediated protective effects in HG-stimulated podocytes may be associated with modulation of autophagy and PI3K/AKT/mTOR signaling pathway.Keywords: diabetic nephropathy, epidermal growth factor, podocyte injury, autophagy, DNA methylation, PI3K/AKT/mTOR